Columellar Lengthening in Primary and Secondary Rhinoplasty for Binder's Syndrome: A Fresh Perspective - Agrawal, Kapil; Shrotriya, Raghav (Indian Journal of Plastic Surgery, 2023)
Binder's syndrome is a developmental disorder with a short columella and nasal base flaring among the many features that have been described. Since the nose occupies the central position over the face, these features appear as a major cosmetic deformity for which patients seek correction. Traditionally various designs of V–Y advancement flap from the upper lip have been described, but they are not without problems. In this article, the authors have discussed a novel design that can mitigate those problems and also described a method of providing additional vascular safety in case of secondary rhinoplasty.
Keywords: rhinoplasty; plastic surgery; binder syndrome; columellar reconstruction; short columella